Using ultrasound to understand acupuncture. - Konofagou, E.E.
For more than two millennia acupuncture has been a widely accepted method for the treatment of acute and chronic disorders in China. Now, acupuncture is becoming increasingly popular in the West and is routinely recommended for the treatment of pain and for relief from the nausea and vomiting associated with chemotherapy, substance dependency, and chronic disorders difficult to manage with conventional treatment. In order to understand the mechanism of acupuncture, ultrasound-based techniques are employed. Ultrasound constitutes an ideal medium for evaluating the biomechanical effects of needle manipulation on tissue. Ultrasound has the unique advantage of yielding both images of tissue morphology and biomechanical information. Inserting the acupuncture needle in vivo under sonogram visualization allows identification of anatomical details, i.e., tissue layers penetrated by the needle. Continuous ultrasound radiofrequency signal acquisition and processing during acupuncture needle movement permits quantitative tissue motion analysis at a varying distance away from the needle using off-line elasticity imaging techniques. Finally, in vitro high-resolution C-scan ultrasound imaging of animal tissue explants can reveal changes in microscopic tissue structure resulting from acupuncture needle manipulation. Imaging of the displacements occurring before and after rotation at a certain amount of revolutions of the needle allowed for the quantitative analysis of the extent of the tissue affected by the needle when it is rotated, as is the case in the clinical practice of acupuncture. It also allowed for temporal monitoring of the tissue behavior around the needle as a result of the type of needle manipulation. Ongoing investigations over a larger pool of human subjects correlating with biochemical and neurological as well as morphological effects are expected to shed important light on the applications of this technique to better interpret the effect of needling on subcutaneous tissues.
Keywords: Acupuncture; Acupuncture needle manipulation; Acute disorders; Animal tissue explants; Biomechanical effects; Chemotherapy; Chronic disorders; Displacements; In vitro high-resolution C-scan ultrasound imaging; Microscopic tissue structure; Nausea; Needle manipulation; Off-line elasticity imaging; Pain treatment; Sonogram visualization; Subcutaneous tissues; Substance dependency; Tissue morphology; Tissue motion analysis; Ultrasound; Ultrasound radiofrequency signal acquisition; Ultrasound radiofrequency signal processing; Vomiting